2013
DOI: 10.1371/journal.pone.0074039
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Astrocytic Response to Cortical Injury

Abstract: Astrocytes are a heterogeneous population of glial cells with multifaceted roles in the central nervous system. Recently, the new method for the clonal analysis Star Track evidenced the link between astrocyte heterogeneity and lineage. Here, we tested the morphological response to mechanical injury of clonally related astrocytes using the Star Track approach, which labels each cell lineage with a specific code of colors. Histological and immunohistochemical analyses at 7 days post injury revealed a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 34 publications
5
61
1
Order By: Relevance
“…This brings us to the next level of analysis, namely aimed at subsets of astrocytes with specific properties. Indeed, astrocytes at juxtavascular positions, the population that is most proliferative after injury (Bardehle et al, ) is a subset with their own progenitors as recently demonstrated by clonal analysis (Martín‐López et al, ). This suggests that juxtavascular astrocytes may be a specific population of cerebral cortex astrocytes and isolation of this subset may then reveal to which extent these share even more similarities to the SEZ NSCs or rather are their own kind.…”
Section: Neural Stem Cell Similarities and Differencesmentioning
confidence: 92%
“…This brings us to the next level of analysis, namely aimed at subsets of astrocytes with specific properties. Indeed, astrocytes at juxtavascular positions, the population that is most proliferative after injury (Bardehle et al, ) is a subset with their own progenitors as recently demonstrated by clonal analysis (Martín‐López et al, ). This suggests that juxtavascular astrocytes may be a specific population of cerebral cortex astrocytes and isolation of this subset may then reveal to which extent these share even more similarities to the SEZ NSCs or rather are their own kind.…”
Section: Neural Stem Cell Similarities and Differencesmentioning
confidence: 92%
“…These proliferative astrocytes were largely localized to juxtavascular sites, indicating that niche-specific cues may direct functional properties of reactive astrocytes (see Box 1). Interestingly, this proliferative population of reactive astrocytes was also shown by clonal analysis to be derived from distinct progenitors 20 , suggesting that one source of reactive astrocyte heterogeneity may be distinct cellular origins. In support of this, neural stem cell (NSC)-derived reactive astrocytes have been shown to contribute to glial scars in the brain 21 , while a recent study found little contribution of NSC-derived reactive astrocytes to SCI-induced glial scars 22 .…”
Section: Functional Diversity Of Glial Cells In the Injured Cnsmentioning
confidence: 97%
“…Indeed, we observed CD45 + cells accumulating in the vessels in conditions with increased astrocyte proliferation, consistent with their failure to infiltrate. Interestingly, juxtavascular astrocytes share a common ancestor during development, as shown by clonal analysis [59], suggesting that they may differ from other astrocytes not only in their position, but also their intrinsic makeup. But which could be the factors of juxtavascular astrocytes regulating monocyte invasion?…”
Section: Astrocyte Proliferation Limits Monocyte Invasionmentioning
confidence: 99%